VIRTUAL DRAMA PERFORMANCE: IS IT A NEED DUE TO PANDEMIC OR TECHNOLOGICAL ERA? - Rita Inderawati; Eryansyah Eryansyah; Dwi Maharrani; Didi Suhendi; Sardianto Siahaan (English Review: Journal of English Education, 2023)
This study aims to address the needs of students in drama and drama performances in the Literature in ELT course. Since the occurrence of a national disaster, namely the spread of the covid-19 virus, the output of the Literature in ELT courses in the form of drama performances cannot be carried out due to the spread of the Covid-19 pandemic. The solution offered through this research is to perform virtual drama performances. The data were obtained through the use of a questionnaire. The data were analyzed both quantitatively and qualitatively. The result of the need analysis showed that: 1) Literature in ELT course was important for the students, 2) students’ English proficiency was at the intermediate level, 3) students still had some difficulties in drama performance, 4) the topic was English legend, 5) there was a need of integrating drama with an online application, 6) students still sometimes learn Literature in ELT with technology. Due to the needs, it was necessary to develop virtual drama performance through online application because 55.5% of students thought that it would increase their knowledge and understanding of the topic in learning Literature in ELT course in university. When offering Literature in ELT course online, it can be noted that the necessary adjustments were made to the theater activities and the drama education program, and the Zoom digital platform was mostly utilized in the online classes.